Green Persuasion Advertising, Voluntarism, and America's Public Lands - Stine, Jeffrey (Open Monographs, 2021)
Green Persuasion traces the history and evolution of volunteer-based public lands stewardship in the United States as well as the Advertising Council's work promoting environmental causes, such as the Smokey Bear fire prevention and the Keep America Beautiful campaigns. The Take Pride in America program, developed during the Reagan administration, was revised, neglected, and readopted by subsequent presidencies. Working with the U.S. Department of the Interior, the Ad Council enlivened the Take Pride initiative with public service announcements featuring celebrity spokespersons Clint Eastwood, Charles Bronson, and Louis Gossett Jr. Green Persuasion offers valuable insights into how and why Americans have expressed care of the nation's landed inheritance in their collective political choices.